Integration of Gender and Development Approach on Institutional Programs, Activities, and Projects of Higher Education Institution: An Input to Strategic Development Plan - Mary Ann Hernandez; Marcial M. Bandoy; Lerma P. Buenvinida (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
The purpose of this paper is to determine the GAD-aligned Programs, Projects, and Activities' gender-related mandated functions and integration. To obtain the necessary information on individuals in Higher Education Institutions based on specific traits and standards and clearly define the institution's long-term direction based on the institution's aims and objectives. Gender and Development focus on Gender Mainstreaming, which is a technique that incorporates both gender concerns and practices into the strategy, execution, supervision, and evaluation of guidelines, processes, plans, and activities at all levels, ensuring that both genders benefit equally. The study used a descriptive methodology to measure the extent to which gender-related activities integrated into mainstreaming mandatory functions and perceptions on GAD-aligned PPAs. There is no significant link between mandated outcome based on HEI-moderated (LUC or SUC) Instruction, Research, Extension, and Resource Management and perceived level of integration on the gender-related functions of Gender and Development Programs, Activities, and Projects, and GAD-aligned PPAs in mainstreaming. The mainstream GAD-aligned PPAs at the university do not predict the integration of GAD-related functions. The SUC/LUC category did not affect the relationship between the GAD-aligned PPAs and the level of integration when it approached the identified indicators.